THE RELATIONSHIP BETWEEN HUSBAND'S SUPPORT AND THE LEVEL OF ANXIETY EXPERIENCED BY PREGNANT WOMEN AT THE ATIKAH CLINIC, PANYABUNGAN DISTRICT, MANDAILIN G NATAL REGENCY YEAR 2025 - Helmi Wardah Nasution; Dewi Srirahayu Tinendung (Benih : Journal of Midwifery, 2025)
Pregnancy is a phase of life accompanied by physical and psychological changes, making pregnant women susceptible to anxiety. One important factor influencing the level of anxiety of pregnant women is the support of their husbands, both emotional, physical, and psychological. Less than optimal support can increase anxiety and negatively impact the health of the mother and fetus. This study aims to analyze the relationship between husband's support and the level of anxiety of pregnant women. This study used a quantitative design with a correlational approach. The study population was pregnant women in the second and third trimesters who checked their pregnancies at the Atikah clinic. A sample of 50 pregnant women was selected using a random sampling technique. The research instruments were a husband's support questionnaire covering emotional, physical, and psychological support, and the Beck Anxiety Inventory (BAI) to measure the level of anxiety of pregnant women. Data analysis was performed univariately and bivariately using the Chi-Square test. The results showed that the majority of respondents received insufficient support from their husbands (60.0%), and the majority of pregnant women experienced moderate levels of anxiety (54.0%). The results of the bivariate analysis showed a significant relationship between husband's support and the level of anxiety of pregnant women (p = 0.003; p < 0.05). Pregnant women who receive good husband support tend to have mild anxiety levels, while those with less husband support are more likely to experience moderate to severe anxiety. The study's conclusions indicate that husband support plays a significant role in reducing maternal anxiety levels. Therefore, increasing husbands' involvement through education and support during pregnancy is necessary as a promotional and preventive measure to maintain the mental health of pregnant women.